Die Beziehungen des Deutschen Ordens zu den Grafen von Kyburg und zur Stadt Bern in der ersten Hälfte des 13. Jahrhunderts - Gotówko, Piotr (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
The relations of the Teutonic Order to the Counts of Kyburg and the city of Bern in the first half of the 13th century As the Teutonic Order began acquitting lands in the south-western part of the Reich and the neighboring Burgundy between 1200‒1212, he depended on the goodwill of the mighty House of Kyburg. Because the Teutonic Brethren were the favorites of their rivals, the Hohenstaufen, it was difficult for them, to gain also their grace. The same applied for the city of Bern, standing under the patronage of the House of Zähringen, other local rivals of the Hohenstaufen. After their line vanished in 1218, the Emperor Frederick II. launched a long struggle with the Kyburgs for the legacy, which took a sharp form especially in Beromünster. This might have influenced the way the members of the Kyburg-Family were looking at the Teutonic Order. When the inheritance of the Zähringen was definitively divided in 1226, the Emperor expropriated in the same year in Köniz the Augustine monks and gave their possessions to the Teutonic Order. Because the church in Bern also belonged to them, the priests of the Order had become the highest clerics in the city. The Emperor wanted thus to keep the Berner patricians in leaning strikes. The simple habitants of Bern had refused to participate at messes celebrated by Teutonic priest for long. The Kyburgs started preferring the Knights of St. John. It was in their church, where the head of the family, Werner I. von Kyburg, was buried after dying from a disease in the Holy Land. The Teutonic Order should never obtain any possessions in territories controlled by the House of the Kyburg.